How does grandparent childcare affect labor supply? - Giulio Zanella (IZA World of Labor, 2017)
Older people in developed countries are living longer and healthier lives. A prolonged and healthy mature period of life is often associated with continued and active participation in the labor market. At the same time, active grandparents can offer their working offspring a free, flexible, and reliable source of childcare. However, while grandparent-provided childcare helps young parents (especially young mothers) overcome the negative effects of child rearing on their labor market participation, it can sometimes conflict with the objective of providing additional income through employment for older workers, most notably older women.
Keywords: J1; J2; J3; J4; J5; J6; 330; grandparents; childcare; work; retirement